Denoising of diffusion MRI improves peripheral nerve conspicuity and reproducibility. Issue 4 (26th October 2019) - Sneag, Darryl B.; Zochowski, Kelly C.; Tan, Ek T.; Queler, Sophie C.; Burge, Alissa; Endo, Yoshimi; Lin, Bin; Fung, Maggie; Shin, Jaemin
Abstract : Background: Quantitative diffusion MRI is a promising technique for evaluating peripheral nerve integrity but low signal‐to‐noise ratio (SNR) can impede measurement accuracy. Purpose: To evaluate principal component analysis (PCA) and generalized spherical deconvolution (genSD) denoising techniques to improve within‐subject reproducibility and peripheral nerve conspicuity. Study Type: Prospective. Subjects: Seven healthy volunteers and three peripheral neuropathy patients. Field Strength/Sequence: 3T/multiband single‐shot echo planar diffusion sequence using multishell 55‐direction scheme. Assessment: Images were processed using four methods: "original" (no denoising), "average" (10 repetitions), "PCA‐only, " and "PCA + genSD." Tibial and common peroneal nerve segmentations and masks were generated from volunteer diffusion data. Quantitative (SNR and contrast‐to‐noise ratio [CNR]) values were calculated. Three radiologists qualitatively evaluated nerve conspicuity for each method. The two denoising methods were also performed in three patients with peripheral neuropathies. Statistical Tests: For healthy volunteers, calculations included SNR and CNRFA (computed using FA values). Coefficient of variation (CV%) of CNRFA quantified within‐subject reproducibility. Groups were compared with two‐sample t ‐tests (significance P < 0.05; two‐tailed, Bonferroni‐corrected). Odds ratios (ORs) quantified the relative rates of each of three radiologists confidently identifying a nerve, per slice, for the four methods. Results: "PCA + genSD" yielded the highest SNR (meanoverall = 14.83 ± 1.99) and tibial and common peroneal nerve CNRFA (meantibial = 3.45, meanperoneal = 2.34) compared to "original" ( P SNR < 0.001; P CNR = 0.011) and "PCA‐only" ( P SNR < 0.001, P CNR < 0.001). "PCA + genSD" had higher within‐subject reproducibility (low CV%) for tibial (6.04 ± 1.98) and common peroneal nerves (8.27 ± 2.75) compared to "original" and "PCA‐only." The mean FA was higher for "original" than "average" ( P < 0.001), but did not differ significantly between "average" and "PCA + genSD" ( P = 0.14). "PCA + genSD" had higher tibial and common peroneal nerve conspicuity than "PCA‐only" (ORtibial = 2.50, P < 0.001; ORperoneal = 1.86, P < 0.001) and "original" (ORtibial = 2.73, P < 0.001; ORperoneal = 2.43, P < 0.001). Data Conclusion: PCA + genSD denoising method improved SNR, CNRFA, and within‐subject reproducibility (CV%) without biasing FA and nerve conspicuity. This technique holds promise for facilitating more reliable, unbiased diffusion measurements of peripheral nerves. Level of Evidence: 2 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;51:1128–1137.